PERANAN KOMPETENSI SUMBER DAYA MANUSIA (SDM) TERHADAP KINERJA KARYAWAN DALAM MENINGKATKAN PROMOSI PRODUK DI PT. PUSRI PALEMBANG - Miftahul Huda; Trisninawati, Trisninawati (Bajang Institute, 2024)
Increased product promotion at PT. Pusri Palembang can be done through the competence of human resources (HR). This study aims to determine the role of human resource (HR) competence on employee performance in improving product promotion at PT. Pusri Palembang. This study used qualitative descriptive method. The results obtained from this study are the role of human resource (HR) competence at PT. Pusri Palembang is very influential in improving product promotion, through training provided by the company